KEPUASAN PELANGGAN MEMEDIASI KUALITAS PRODUK DAN KEWAJARAN HARGA TERHADAP LOYALITAS MEREK MCDONALDS DI KOTA DENPASAR - Wijaya, I Putu Surya Ananta; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 6 No 3 (2017), 2017)
McDonalds has the highest level of sales among its competitors in Denpasar. This study is intended to look at the role of customer satisfaction mediates the effect of product quality and reasonableness of the price on brand loyalty McDonalds fast food restaurant in the city of Denpasar. Through purposive sampling method specified sample size of 100 respondents. Collecting data using questionnaires. SEM analysis techniques and Sobel test used in this study. These results demonstrate the quality of the product has a positive and significant impact on customer satisfaction and brand loyalty, price reasonableness influence on customer satisfaction and brand loyalty has a positive and significant influence, and there is positive and significant correlation between customer satisfaction on brand loyalty. Customer satisfaction does not directly influence and unable to mediate the effect of product quality and fairness of the price on brand loyalty. Loyal customer attitudes toward a brand is indicated by how much intensity caused repeated purchases on consumer satisfaction.
Keywords: brand loyalty; product quality; customer satisfaction; price reasonableness